Medkulturne identitete Italijanov v romanih Travniška kronika (Travnička hronika) Iva Andrića in Turško ogledalo (Török tükör) Viktorja Horvata - Francišković, Dragana (Slavistična revija, 2016)
The author discusses intercultural identity of Italians appearing in the novels Bosnian Chronicle (Travnička hronika) by Ivo Andrić and Turkish mirror (Török tükör) by Viktor Horváth. The two novels have several common traits. Multicultural environments monitor the reflections on social breakdowns and react to them with their previously acquired mechanisms.
Keywords: "Török tükör"; "Travnička hronika"; Andrić, Ivo, 1892-1975; compative studies; Horváth, Viktor, 1962-; Hungarian literature; Italians; Italijani; madžarska književnost; multiculturalism; multilingualism; novel; primerjalne študije; roman; Serbian literature; srbska književnost; večjezičnost; večkulturnost